INFLUENCE OF THE TURBULENCE MODEL ON THE NUMERICAL PREDICTIONS OF THE CAVITATING FLOW AROUND A HYDROFOIL - Morgut, Mitja; Nobile, Enrico (Journal of Energy Technology, 2024)
In this paper, the influence of the turbulence model on the numerical predictions of the cavitating flow around a hydrofoil is investigated. The flow is modelled using the RANS (Reynolds Averaged Navier-Stokes) approach in combination with the interphase capturing VOF (Volume of Fluid) method. The study is carried out considering the cavitating flow around the NACA66(MOD) hydrofoil at two angles of incidence and employing three widespread turbulence models. The numerical results show that the turbulence model may play a minor role for the prediction of the stable sheet cavity flow over a hydrofoil.